Inovasi Asesmen Digital MyPatriotik: Pendekatan Gamified Chunking untuk Mengurangi Overload Kognitif dan Meningkatkan Sikap Patriotik Mahasiswa - BATUBARA, ABDINUR (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2026)
This study aims to validate the effectiveness of the digital assessment innovation, MyPatriotik, which integrates gamification and chunking principles, in simultaneously enhancing students' patriotic attitude and mitigating Extraneous Cognitive Load (ECL) in Civic Education (PPKn) learning. The research utilized a quantitative approach with a Pre-test Post-test Control Group Design, involving 80 PPKn students from UNIMED, split into an experimental group (using MyPatriotik) and a control group (conventional assessment). The findings revealed a statistically significant difference (sig. = 0.000) between the two groups. The experimental group showed a substantially higher increase in patriotic attitude and a sharp reduction in ECL compared to the control group. This success confirms the novelty of using gamification (realtime 1 vs 1 challenge) to boost affective engagement and chunking (in study materials) to optimize cognitive architecture by alleviating unnecessary cognitive burden. MyPatriotik offers a new pedagogical framework, transforming traditional assessment into an active catalyst for building national commitment and solving the issue of high ECL, aligning with the goal of quality education. Future research should focus on the long-term sustainability of these affective and cognitive gains.